Approaches towards Land Valuation and Land Pricing under the Influence of Geo-Climate Change - Josef Slaboch; Michal Malý (Agriculture, 2022)
The Czech Republic is more or less unique in its dual system (official and market price) of agricultural land prices. In the case of the market price, there are several studies and approaches that assess the impact of individual variables on the market price of land. If we focus on the official price of land, its value in the Czech Republic is influenced by the evaluated soil ecological unit (ESEU) price. The ESEU price expresses the production potential of the land on the basis of soil quality indicators, which include the climatic region, the main soil unit, slope and exposure and, last but not least, the depth of the soil profile and skeletonisation. Climate change also means that the current values of the definition (e.g., for a climatic region, this refers to the average temperature or average precipitation) do not correspond to reality. No studies have looked in detail at the impact of soil quality indicators or climate change on the price of ESEUs. New and more accurate measurements of soil characteristics are increasing the number of ESEU codes, and prices have not yet been set for some codes. For this reason, we proposed the use of a hedonic method to determine shadow prices, which reflect the intensity and direction of the effect of each input variable on the price of an ESEU. A heteroscedastic corrected linear regression model was used to determine the coefficients, which presents in detail the effect of all included parameters on the final price of an ESEU in the results section. From the results, it was obvious that the shadow price coefficients themselves corresponded to basic generally accepted assumptions regarding the direction of effect. In the conditions of the Czech Republic, a significant influence on the price of an ESEU was mainly the slope with exposure and the depth of the soil profile with skeletonisation. These factors affected the productive capacity of the soil, which, in turn, translated into lower profitability of agricultural entities. The high explanatory ability of the hedonic model, with a high parametric significance for most of the used variables, was an important factor determining the robustness of the model as a repricing tool. The model set according to the prices of the applicable price decree can be used to set the prices of new or not-yet-valued ESEU codes under the conditions in the Czech Republic, or shadow prices can be used during climatic changes in the event of the transfer of the given soil unit to another climate region according to the general specification. It is therefore an important tool for the needs of the public administration.